Risk Analysis of Combustion Failure in Gas Turbine Start Process in PLTGU Unit PT.X - Muhammad Syaifuddin Zuhdi; Mokh. Suef (IPTEK Journal of Proceedings Series, 2019)
The peaker power plant is a power plant that is operated when the network is at peak load. Being a peaker power plant has an impact more often start- stop for operation of gas turbine. So, the readiness of the gas turbine to start any time is the core business of the peaker power plant. But in reality, start failure still occurs in the generating unit. Start failure can be caused by combustion failure. In 2017 and 2018 years, there was a start failure caused by combustion system failure total 10 out of 19 cases internal start failure. A lot of disadvantages of start failure for the company like very much loss of potential production revenue, loss of fuel consumption, electricity usage for supporting equipment, materials of gas turbine, failure to achieve KPI’s company, decrease in customer satisfaction and much more. So, it must be minimized or eliminated. Until now, maintenance for start failure still corrective maintenance. Corrective maintenance is an unscheduled, unpredictable, unplanned or unprogrammed maintenance action based on an event at a certain time so the potential loss of company’s income large. One effort to reduce corrective maintenance activities with preventive maintenance. However, to do preventive maintenance, it is necessary to conduct in-depth studies and analysis so that preventive maintenance is carried out effectively and on target. For this reason a risk analysis of the combustion failure with Failure Mode and Effects Analysis (FMEA) method need to do, so the preventive maintenance steps can be obtained to mitigate the risk of start failure in gas turbine power plant. From the result of FMEA, there are two extreme risk from combustor system, igniter and fuel valves. So, preventive maintenance applied to them. It can provide a large potential revenue for industry and company reputation